PENGARUH ARANG AKTIF DALAM CAMPURAN BAHAN BAKU TERHADAP KARAKTERISTIK PAPAN PARTIKEL - Adi Santoso; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2012)
Formaldebyde emission andpbysical-mechanical properties of particleboard bonded with urea formaldehyde (UF) could have negative effects to buman bealth, especially when used in a room with limited ventilation. To reduce formaldebyde emission, anadsorbentcan be applied to raw material as a mixture. This report describes the effect of active charcoal application on formaldehyde emission and physical-mechanical properties of the bonded particleboard. Results showed that application of active charcoal in particleboard production significant changed the product properties. Active charcoal addition as much as 20% of the particle weight to raw material could reduce formaldebryde emission andincreaseplrysical-mechanical propertiesof particleboard, and meet the Indonesian and Japanese Standards.